2019
DOI: 10.3390/biology8040082
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in Cancer Cell Death

Abstract: Autophagy has important functions in maintaining energy metabolism under conditions of starvation and to alleviate stress by removal of damaged and potentially harmful cellular components. Therefore, autophagy represents a pro-survival stress response in the majority of cases. However, the role of autophagy in cell survival and cell death decisions is highly dependent on its extent, duration, and on the respective cellular context. An alternative pro-death function of autophagy has been consistently observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 92 publications
1
51
0
8
Order By: Relevance
“…[ 228 , 229 ]. Autophagic cell death is important in reducing the viability of cancer cells [ 230 , 231 ]. Chrysin enhances levels of light chain-3 II (LC-3II) to induce autophagy.…”
Section: Chrysin and Cancermentioning
confidence: 99%
“…[ 228 , 229 ]. Autophagic cell death is important in reducing the viability of cancer cells [ 230 , 231 ]. Chrysin enhances levels of light chain-3 II (LC-3II) to induce autophagy.…”
Section: Chrysin and Cancermentioning
confidence: 99%
“…Autophagy can have dual roles in the context of cancer as mentioned above it may have prosurvival effects and on the other hand it is also recognized as a cell death pathway. Long-lasting activation of the autophagosomal/lysosomal pathway can lead to autophagic cell death [ 25 ]. In vitro experiments show that high doses of DNA damaging cytostatics induce autophagic cell death [ 26 ].…”
Section: Lysosomes V-atpases and Cancermentioning
confidence: 99%
“…Some authors have actually observed that the depletion of autophagy decreased the viability of chronic myeloid leukemia CD34+ progenitor cells, whereas its inhibition in hematopoietic stem cells (HSC) has favored the development of hematopoietic diseases (Auberger and Puissant, 2017;Levine and Kroemer, 2019). On the other hand, after treatment with synthetic or natural compounds, there are some evidences that when the autophagosomal/lysosomal pathway is over activated for a prolonged time the autophagic cell death (ACD, type II cell death) can occur (Liao et al, 2019;Linder and Kögel, 2019). Arsenic trioxide (ATO) has been proved to induce ACD in several cancer cells.…”
Section: Autophagy In Cancermentioning
confidence: 99%